Silk fibroin/cholinium gallate-based architectures as therapeutic tools. (15th July 2022) - Gomes, Joana M.; Silva, Simone S.; Fernandes, Emanuel M.; Lobo, Flávia C.M.; Martín-Pastor, Manuel; Taboada, Pablo; Reis, Rui L.
Abstract: The combination of natural resources with biologically active biocompatible ionic liquids (Bio-IL) is presented as a combinatorial approach for developing tools to manage inflammatory diseases. Innovative biomedical solutions were constructed combining silk fibroin (SF) and Ch[G allate ], a Bio-IL with antioxidant and anti-inflammatory features, as freeze-dried 3D-based sponges. An evaluation of the effect of the Ch[Gallate] concentration (≤3% w/v) on the SF/Ch[Gallate] sponges was studied. Structural changes observed on the sponges revealed that the Ch[Gallate] presence positively affected the β-sheet formation while not influencing the silk native structure, which was suggested by the FTIR and solid-state NMR results, respectively. Also, it was possible to modulate their mechanical properties, antioxidant activity and stability/degradation in an aqueous environment, by changing the Ch[Gallate] concentration. The architectures showed high water uptake ability and a weight loss that follows the controlled Ch[Gallate] release rate studied for 7 days. Furthermore, the sponges supported human adipose stem cells growth and proliferation, up to 7 days. TNF-α, IL-6 (pro-inflammatory) and IL-10 (anti-inflammatory) release quantification from a human monocyte cell line revealed a decrease in the pro-inflammatory cytokines concentrations in samples containing Ch[G allate ]. These outcomes encourage the use of the developed architectures as tissue engineering solutions, potentially targeting inflammation processes. Statement of Significance: Combining natural resources with active biocompatible ionic liquids (Bio-IL) is herein presented as a combinatorial approach for the development of tools to manage inflammatory diseases. We propose using silk fibroin (SF), a natural protein, with cholinium gallate, a Bio-IL, with antioxidant and anti-inflammatory properties, to construct 3D-porous sponges through a sustainable methodology. The morphological features, swelling, and stability of the architectures were controlled by Bio-IL content in the matrices. The sponges were able to support human adipose stem cells growth and proliferation, and their therapeutic effect was proved by the blockage of TNF-α from activated and differentiated THP-1 monocytes. We believe that these bio-friendly and bioactive SF/Bio-IL-based sponges are effective for targeting pathologies with associated inflammatory processes. Graphical abstract: Image, graphical abstract